KAJIAN KRITIS TERHADAP EPISTIMOLOGI ILMU: TEORI PENGETAHUAN DAN METODE ILMIAH - Iqbal, Aji Muhammad (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
ABSTRACKIn everyday life humans often encounter phenomena that make humans feel amazed, astonished. It gives rise to man's curiosity about the symptoms of nature or humans want to try to find answers to the problems they face. In essence, we expect the right answer, and not just an answer that is just any. . Then there is the problem, how do we develop the right knowledge. It is this problem that in the study of philosophy is called epistemology, and the basis of scientific epistemology is the scientific method. This research is a library research or literature research that is a problem and the collection of research data is sourced from primary data (principal) and secondary data (supporting data) sourced from literature in the form of books, journals, and other publications. It can be seen that Knowledge is everything that mabusia captures about objects as a result of the process of knowing, both through the senses and the sense. The method for finding it can be seen with the scientific method. The practice of the field is called scientific activity, a work that is constantly conducting scientific research to achieve the truth.